2023
DOI: 10.1101/2023.03.31.535146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role for cytoglobin in regulating intracellular hydrogen peroxide and redox signals in the vasculature

Abstract: The oxidant hydrogen peroxide serves as a signaling molecule that alters many aspects of cardiovascular functions. Recent studies suggest that cytoglobin, a hemoglobin expressed in the vasculature, may promote electron transfer reactions with proposed functions in hydrogen peroxide decomposition. Here, we determined the extent to which cytoglobin regulates intracellular hydrogen peroxide and established mechanisms. We found that cytoglobin decreased the hyperoxidation of peroxiredoxins and maintained the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Overall, these results suggest that cytoglobin is required in the nucleus to affect gene programs related to DNA repair and mitigate both oxidant and replicativeinduced DNA damage. Moreover, we show that these effects occur through a mechanism separate from the previously established oxidant scavenging activity of cytoglobin 10 .…”
Section: Cytoglobin Affects Dna Repair Pathways and Inhibits Dna Dama...supporting
confidence: 49%
See 4 more Smart Citations
“…Overall, these results suggest that cytoglobin is required in the nucleus to affect gene programs related to DNA repair and mitigate both oxidant and replicativeinduced DNA damage. Moreover, we show that these effects occur through a mechanism separate from the previously established oxidant scavenging activity of cytoglobin 10 .…”
Section: Cytoglobin Affects Dna Repair Pathways and Inhibits Dna Dama...supporting
confidence: 49%
“…As such, cytoglobin has been proposed to regulate NO dependent-vasorelaxation and NO-dependent cytotoxicity in vessels during conditions associated with increased inducible NO synthase (NOS2) expression 4,8,9 . More recently, we found that isolated vessels from cytoglobin knockout mice also displayed decreased rates of hydrogen peroxide consumption, suggesting a role for cytoglobin as a peroxidase in the vasculature 10 . In models of vascular injury, we proposed that loss of cytoglobin limited the survival capacity of a cell population that expresses cytoglobin 2-3 days after initiation of the injury 9 .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations